Strengthening of shear-deficient RC beams using near surface embedded precast cement-based composite plates (PCBCPs). (1st October 2021) - Afefy, Hamdy M.; Baraghith, Ahmed T.; Hassan, Ali; Abuzaid, Mohamed K.
Highlights: Precast cement-based composite plates (PCBCPs) have been prepared and cured. PCBCPs composed of SHCC material reinforced with internal mild steel plates. PCBCPs have been used for Strengthening of shear-deficient RC beams. Experimental tests results confirmed the capability of the adopted technique. Inclined arrangement of the PCBCPs resulted in outstanding performance for RC beams. Abstract: Precast cement-based composite plates (PCBCPs) have been prepared, cured and then used to strengthen shear-deficient reinforced concrete (RC) beams. The used PCBCPs have rectangular cross-sections of 100 mm width and 20 mm thickness made of strain-hardening cementitious composite (SHCC) material and reinforced with mild steel plates of 1 mm thickness having variant reinforcement ratios (1.4, 2.8, and 4.2%). The motivation of using such reinforced composite plates is to make use of the mutual benefits between the used materials where the internal steel plate alleviates the cracks localization manifested by plain SHCC material after cracking, while the SHCC material protects the steel plates against corrosion. Experimental test results showed that the use of PCBCPs significantly increased the ultimate shear capacity of the strengthened beams. Besides, inclined configuration of the PCBCPs showed higher shear performance compared to that exhibited by the vertical configuration from both the ultimate capacity and shear cracks characteristics viewpoints. Beam B3-56-100-45 strengthened by inclined PCBCPs showed the best performance among all tested beams. It exhibited about 126% increases in the ultimate capacity compared to that of the control un-strengthened beam. On the other hand, the corresponding increase of counterpart beam reinforced with vertical plates was about 88%.